Methods of testing plastics. Chemical properties. Determination of formaldehyde in phenolic mouldings (colorimetric method). Determination of formaldehyde in phenolic mouldings (gravimetric method). Determination of sulphates in phenolic mouldings. Determination of chlorides in phenolic mouldings Part 4, (28th February 1978) - British Standards Institution,
No abstract available